Metabolomika - základní pojmy, strategie a metodologie - Musilová, Jindra; Glatz, Zdeněk (Chemické listy, 2011)
This review defines metabolomics and clarifies its history and significance. Various strategies of metabolomics research are described together with their main application fields. The review focuses on the methods of sample preparation and on the analytical methodologies that are most frequently used in metabolomic studies  NMR, MS, GC/MS, HPLC/MS and CE/MS. Practical importance of metabolomics and its role in system biology are mentioned as well.
Keywords: chromatografie kapalinová; Electrophoresis, Capillary; Computational Biology; chromatografie plynová; Chromatography, Gas; Magnetic Resonance Spectroscopy; magnetická rezonanční spektroskopie; Metabolome; metabolomika; Metabolomics; Chromatography, Liquid; metabolom; elektroforéza kapilární; výpočetní biologie